2021
DOI: 10.3390/ani12010048
|View full text |Cite
|
Sign up to set email alerts
|

T329S Mutation in the FMO3 Gene Alleviates Lipid Metabolic Diseases in Chickens in the Late Laying Period

Abstract: The T329S mutation in flavin-containing monooxygenase 3 (FMO3) impairs the trimethylamine (TMA) metabolism in laying hens. The TMA metabolic pathway is closely linked to lipid metabolic diseases, such as atherosclerosis and fatty liver disease. We aimed to evaluate the effects of the T329S mutation in FMO3 on lipid metabolism in chickens during the late laying period. We selected 18 FMO3 genotyped individuals (consisting of six AA, six AT, and six TT hens) with similar body weight and production performance. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 48 publications
3
6
1
Order By: Relevance
“…Accordingly, the decreased trends of TC and LDL-C levels of TT hens explained the decrease in AS lesions. However, the observed trend of plasma VLDL levels of TT hens is inconsistent with that of our previous study, which showed that TT hens have higher VLDL levels at 62 weeks ( 19 ). This might be related to hepatic TG secretion because VLDL is the major transport vehicle for TG from the liver to extrahepatic tissues, or it might be attributable to the dynamic change of VLDL subclasses in layers during the normal aging process ( 25 , 41 ).…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Accordingly, the decreased trends of TC and LDL-C levels of TT hens explained the decrease in AS lesions. However, the observed trend of plasma VLDL levels of TT hens is inconsistent with that of our previous study, which showed that TT hens have higher VLDL levels at 62 weeks ( 19 ). This might be related to hepatic TG secretion because VLDL is the major transport vehicle for TG from the liver to extrahepatic tissues, or it might be attributable to the dynamic change of VLDL subclasses in layers during the normal aging process ( 25 , 41 ).…”
Section: Discussioncontrasting
confidence: 99%
“…During the present study, our results showed that the T329S mutation in FMO3 decreased the AL and AAL in TT hens compared to those in AA and AT hens at 90 weeks. This result is consistent with our previous observations, which showed that T329S reduced AS lesions in a strain of chickens laying brown eggs at 62 weeks ( 19 ). This result can be attributed to T329S diminishing the activity of the TMAO-generating enzyme FMO3 and therefore decreased the plasma circulating TMAO concentrations in TT hens.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations